Modernising the education sector in Trinidad : a political perspective on constraints to policy implementation - Taylor, Kenwyn (2008)
Outlines a view of a political perspective on policy implementation in an attempt to examine Trinidad and Tobago government's Vision 2020 modernising education policy, which is in the process of being implemented.